Outpatient “Specialist Practitioners” in Italy in the years before and after the COVID-19 pandemic. The case of the Piedmont Region. - Visca, Giorgio; Angelone, Lorenzo; Obrizzo, Renato; Magi, Antonio (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Aim. Outpatient Contracted Specialist care represents in Italy, together with Family Medicine and Paediatrics, one of the three fundamental pillars of primary and community healthcare. Like General Practitioners of the National Health Service in England and Italy, these “Specialist Practitioners”, mostly medical doctors but also Psychologists and other professionals, play a key role in the management of chronic patients in community settings, as in a “barefoot specialists” model.Few data are however available to precisely define their workforce “input” in community and hospital settings. To partially overcome this issue, the Regional Joint Committee for Outpatient Contracted Specialists of the Piedmont Region has conducted since 2017 an annual survey to monitor the amount of healthcare hours delivered for each specialty. The present study describes the results of the data analysis from 2017 to 2023, also as compared to the visits provided before and after the COVID-19 pandemic. Subject and Methods. Data were gathered through electronic spreadsheets submitted annually by each regional Local Health Authority to the Committee. Regional totals were compared to the available national totals for the year 2023. Finally an analysis was performed on the available data on first visits provided by Local Health Authorities and Hospital Trusts and on booked first visits per inhabitants in 2023.Results. From 2017 to 2023, the weekly hours of Outpatient Contracted Specialist medical care regionally provided declined from 20,535 to 17,264 (-15.93%). The greatest reductions were recorded for Dentistry, Dermatology and Ophthalmology. In contrast, the hours delivered by contracted psychologists increased from 8,136 to 9,532 (+17.16%). In 2023 the provision of Outpatient Contracted Specialist medical care per inhabitants in Piedmont was 34.66% lower than the national average, whereas Psychologists’ hours were 199.12% higher. Vacant medical weekly hours increased from 856 to 2,940 (+243.46%) reaching 14.74% of the total hours of Outpatient Contracted Specialist medical care demanded by Local Health Authorities in 2023. Local Health Authorities’ demand for Outpatient Contracted Specialist Medical Care in the years 2017-2023 went down by 5.05%. The lowering was recorded mainly for Dentistry, Obstetrics & Gynaecology, Psychiatry and Child Neuropsychiatry. The number of first visits provided by Local Health Authorities in the first semester of 2023 was 27.34% lower than that of 2018. In contrast, an increase of 4.18% was observed in the number of first visits provided by Hospital Trusts. The number of Local Health Authorities’ booked first visits every 1,000 inhabitants in 2023 was 34.48% lower than the average national number and more than two-thirds lower than that of a neighbouring region.Conclusions. This study highlights a progressive decline in the public provision of Outpatient Contracted Specialist medical care in Piedmont during the years 2017-2023, despite the increase of waiting lists lengths, out-of pocket private expenditure and renounce to health services. The phenomenon has been enhanced, but not induced, by the COVID-19 pandemic and had its origins mainly in the lack of medical applications, in the shifting of part of financial resource towards psychologic care, but also in an objective decline in the demand of medical job positions from regional Local Health Authorities. The observed reduction is likely to hinder access to public outpatient specialist medical care, mostly in community settings, and to undermine basically the implementation of Proximity Health Networks as outlined in Ministerial Decree n. 77 of 2022.